Left inguinal hernia mimicking metastasis on bone scan - Goel, Sumina (Elsevier, 2015)
Inguinal hernia is a well-known entity that usually affects males. The most common herniated organs are parts of the bowel, omentum, or fat. Urinary bladder herniation into the inguinal region is very rare and is often diagnosed during inguinal hernia surgery. This case highlights the importance of additional views and anatomic imaging to accurately interpret the unusual scan findings.